2021
DOI: 10.3390/diagnostics11071142
|View full text |Cite
|
Sign up to set email alerts
|

PSMA-PET/CT in Patients with Recurrent Clear Cell Renal Cell Carcinoma: Histopathological Correlations of Imaging Findings

Abstract: PET/CT with prostate-specific membrane antigen (PSMA)-targeted tracers has been used in the diagnosis and staging of patients with clear cell renal cell carcinoma (ccRCC). For ccRCC primary tumors, PET parameters were shown to predict histologic grade and features. The aim of this study was to correlate PSMA PET/CT with histopathological findings in patients with metastatic recurrence of ccRCC. Patients with ccRCC who underwent PSMA-targeted PET/CT and subsequent histopathological evaluation of suspicious lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 20 publications
(23 reference statements)
1
39
1
Order By: Relevance
“…Günhe et al looked into the correlation of PSMA PET results and antigen expression in metastatic ccRCC. PSMA expression was confirmed with immunohistochemistry in all metastatic lesions, although intensity and distribution did not correlate with PET parameters [ 30 ]. The authors of this study concluded that despite the value of PSMA PET in the clinical evaluation of these patients, it cannot reliably predict histologic features of metastases.…”
Section: Psma Pet/ct In Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…Günhe et al looked into the correlation of PSMA PET results and antigen expression in metastatic ccRCC. PSMA expression was confirmed with immunohistochemistry in all metastatic lesions, although intensity and distribution did not correlate with PET parameters [ 30 ]. The authors of this study concluded that despite the value of PSMA PET in the clinical evaluation of these patients, it cannot reliably predict histologic features of metastases.…”
Section: Psma Pet/ct In Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“…However, the application of pet clinical examination imaging technology can show the erosive lesions, atrophic lesions and diffuse lesions through imaging. The application of PET imaging in gastric cancer is also discussed in the study on the relationship between PET/CT imaging and the expression of HER2 and MDR1 in gastric cancer published by [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with metastatic disease, PSMA PET/CT has demonstrated a very high detection rate (Rowe et al 2015 ; Meyer et al 2019 ; Raveenthiran et al 2019 ; Gühne et al 2021 ). In this subset of patients, a possible future role for PSMA imaging may be in the therapy response evaluation.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…More recently, Guhne and colleagues (Gühne et al 2021 ) correlated [ 68 Ga]-PSMA PET/CT uptake and histopathological findings in 9 patients with suspect metastatic recurrence of ccRCC. Eleven PSMA-positive lesions were confirmed as metastases from RCC, while 1 lesion resulted from prostate cancer.…”
Section: Methodsmentioning
confidence: 99%